PREFERENSI PERMINTAAN MASYARAKAT TERHADAP PENGGUNAAN BIBIT UNGGUL TANAMAN HORTIKULTURA DI UPT. BIH GEDUNG JOHOR DINAS TANAMAN PANGAN DANHORTIKULTURA PROVINSI SUMATERA UTARA - Nelly Marina Rawaty Sinaga; wilmar saragih; posman HP Marpaung; Razeky Martini Marpaung (Universitas Quality, 2021)
The objectives of the study were to determine (1) the development index of superior horticultural seeds, (2) the elasticity of demand for superior seeds of horticultural crops, and (3) the factors that influence the preference of people's demand for the use of superior seeds of horticultural crops. The research was carried out at UPT.BIH Johor Building, Food Crops and Horticulture Research Office, starting from April to July 2020. The number of samples was 10 people, consisting of 6 UPT staff. BIH Johor Building Department of Food Crops and Horticulture and 4 consumers. Data analysis methods used are development index, elasticity of demand and multiple regression analysis. The results showed that the development index of superior seeds in the study area decreased in 2019, the demand for superior seeds with Ed > 1. Partial t-test showed that the factor of seed prices, income levels and community tastes had a significant effect on demand for seed use, while the number of population has no significant effect. The F test shows that the seed factor, income level, people's tastes, and the number of residents simultaneously (simultaneously) affect the demand for superior seeds. The coefficient of determination test (R2) shows that the price of superior seeds, income levels, people's tastes, and population affects the demand for the use of superior seeds by 85.2%, while the remaining 14.8% is influenced by other factors outside of this study.